2021
DOI: 10.1111/nuf.12568
|View full text |Cite
|
Sign up to set email alerts
|

Nursing student experiences of remote learning during the COVID‐19 pandemic

Abstract: Background The emergence of the COVID‐19 pandemic resulted in a sudden transition to remote learning. These circumstances presented many challenges for higher education faculty and students around the world but especially for nursing education programs which are traditionally conducted in a face‐to‐face learning environment that includes hands‐on experiential learning. Methods Guided by Meleis' Transition Theory, a qualitative descriptive design was utilized to explore prelicensure nursing students’ experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
162
1
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(205 citation statements)
references
References 23 publications
20
162
1
22
Order By: Relevance
“…International studies have demonstrated that, in addition to psychological distress, student nurses also suffered from other psychological problems during the pandemic, including emotional and social loneliness, post-traumatic stress disorder, emotional exhaustion, depression and fatigue ( Grande et al, 2021 , Savitsky et al, 2020 , Labrague et al, 2021 ). Stress associated with distance learning and the abrupt shift to online learning were also seen to contribute to mental and psychological issues in student nurses ( Wallace et al, 2021 , Masha'al et al, 2020 ). In a broad review by Majrashi et al (2021) , stress that stemmed from distance learning was identified as the top stressor among student nurses during the coronavirus pandemic, followed by heavy workload and extreme fear of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…International studies have demonstrated that, in addition to psychological distress, student nurses also suffered from other psychological problems during the pandemic, including emotional and social loneliness, post-traumatic stress disorder, emotional exhaustion, depression and fatigue ( Grande et al, 2021 , Savitsky et al, 2020 , Labrague et al, 2021 ). Stress associated with distance learning and the abrupt shift to online learning were also seen to contribute to mental and psychological issues in student nurses ( Wallace et al, 2021 , Masha'al et al, 2020 ). In a broad review by Majrashi et al (2021) , stress that stemmed from distance learning was identified as the top stressor among student nurses during the coronavirus pandemic, followed by heavy workload and extreme fear of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Nursing education is unique in that it is primarily offered in-person, with a reliance on hands-on learning ( Michel et al, 2021 ; Wallace et al, 2021 ). When the COVID-19 pandemic began in Spring 2020, nursing programs had to rapidly shift from in-person to remote learning due to infection fears and limited personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%
“…Part of these perceptions and relationships are already described in very recent literature regarding academic adjustment in the pandemic [48][49][50][51][52][53]. Still, one should notice that this is a very new research field, with a lot of space for investigation.…”
Section: Introductionmentioning
confidence: 86%